MEMBANGUN PAPUA DENGAN “HATI” - ACHMADY, LA (DINAMIS, 2020)
Development in the land of Papua has been conducted by the government, both physical and non-physical development, but until now still we hear at various occasions about the statements as follows that the government failed to “ Indonesianize” the indigenous Papuans, or “Papuans ohave not felt as part of Indonesia”. Papua has been a part of the Unitary Sate of the Republic of Indonesia for 57 years, but in reality the expression of the above statement is happening and increasing in line with events lately. Of course the situasion is a huge question in ous minds : Why does it happen? The condition should be a torment with maturity and create corrections for improvement, especially a non-physical development approach that is assessed by various parties less concerned if not tobe said to ignore. Some approaches are intentionally expressed as input to local and central stakeholders or anyone living in the land of Papua. These approaches are the records of the task of a community servant, experience, obsevations in various places, discussions and from various references. Intergroup handling approach “ Migrants and indigenous Papuans”. Should prioritize “win-win”, The desired leadership of Papua natives, leadership with “Heart”, Anthropological approach according to local customs/wisdom begins with lifting/empowering what the indigenous Papuans have. Moreover, a religious massage of a pastor in the past uttered : “Whosoever work in this land faithfully, honestly, and lend-an-ear-to, then he will walk from one sign of wonder to others” (Izaak Samuel Kijne, 1947)